The influence of prior creep damage on the fracture localisation in X20 CrMoV12-1 cross-weld creep tests - Rasiawan, Trisha (Centre for Materials Engineering, 2018)
Many of Eskom's coal fired power plants have an average age of 170 000 hours and a few operating close to 300 000 hours. Main steam temperatures experienced in a power plant vary between 535-555°C. These operating conditions place main steam pipe components to operate within the creep regime. It is of utmost importance for safety and plant health that these critical components are managed to determine the remaining life and risks associated with high temperature exposure for prolonged periods of time. Non-destructive testing (NDT) methods are utilised extensively on Eskom power plants to determine the remaining life and replacement strategies for critical components. Surface replication is used as a life assessment tool for creep damage quantification of main steam pipe work. A large part of maintaining plant is repair welding on creep aged and sometimes creep aged material as entire system replacements are impractical and time consuming. By repair welding new material onto creep aged material, mechanical and microstructural properties of the creep aged material deteriorates. The study of this work is focused on characterising the as-received materials from Eskom power plants and using these creep aged materials to create cross-weld samples with virgin material. The cross-weld samples were creep-rupture tested at high temperature and low stress conditions to determine the fracture location of repair welded cross-weld samples. Once ruptured, the zone of rupture, was identified and created in a larger volume by simulation using Gleeble® thermo-mechanical equipment. The as-received base materials were subjected to different operating conditions hence contain different degrees of creep damage. The microstructural evaluation of the creep damaged material was conducted using optical microscopy, scanning electron microscopy (SEM), coupled with more advanced electron backscattered diffraction (EBSD). Microhardness and hot tensile testing were included to characterise the mechanical degradation of the as-received material. The fracture location of the creep-ruptured cross-weld samples were investigated using optical microscopy, SEM and EBSD and occurred on the outer region of the heat affected zone (HAZ) of the creep aged material. The fine grained microstructure with coarse precipitation of this region is characteristic of the fine grain heat affected zone (FGHAZ). The occurrences of voids predominantly occur in this narrow region with very few voids in the adjacent base/weld material. As this zone is of particular interest due to it being the weakest region in repair welded joints, the need to investigate it further is important. A larger testing volume of the FGHAZ was created by applying a weld thermal cycle simulation to the as-received base materials. The impact of this simulation was determined microstructurally by optical microscopy and mechanically by hardness and tensile testing. The FGHAZ has low creep resistance and is most susceptible to failure due to the small grained microstructure. Due to the numerous small grains, there is a high effective diffusion coefficient (HEDC). The multi axial stresses induced during in service/ creep testing conditions together with the HEDC causes voids to form at an accelerated rate. Significant void coalescence promotes the formation of micro cracks which in turn lead to macro crack formation and eventually failure.